In vitro evaluation of a self-positioning individualized titanium mesh for improved accuracy in guided bone regeneration - Zhang, Jiayuan; Chen, Yufan; Tao, Xingru; Zhang, Kaihang; Xu, Chunfeng; Yu, Dedong (Frontiers in Bioengineering and Biotechnology, 2026)
IntroductionAdequate bone volume and contour are essential for successful implant placement. This study evaluated the accuracy of a novel self-positioning three-dimensional printed individualized titanium mesh (3D-PITM) in guided bone regeneration (GBR).MethodsTen identical maxillary phantoms with standardized defects were divided into an experimental self-positioning 3D-PITM group and a conventional 3D-PITM group. Pre- and postoperative CBCT scans were obtained for 3D reconstruction and superimposition. Deviations in augmented contours, screw placement, volumetric accuracy, and 2D cross-sectional augmentation were analyzed.ResultsThe self-positioning group showed significantly reduced deviation in augmentation contours (0.82 ± 0.07 mm vs. 1.02 ± 0.13 mm, P = 0.003), improved screw placement accuracy (0.10 ± 0.13 mm vs. 0.65 ± 0.32 mm, P = 0.026), and lower volumetric discrepancies. Two-dimensional evaluation confirmed greater vertical and horizontal accuracy in bone augmentation (P = 0.021, P = 0.018).ConclusionThe self-positioning 3D-PITM achieved more accurate installation and predictable bone augmentation in vitro, suggesting potential clinical advantages for implant-supported rehabilitation.